If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + -3 = 1x + 7 Reorder the terms: -3 + 2x = 1x + 7 Reorder the terms: -3 + 2x = 7 + 1x Solving -3 + 2x = 7 + 1x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. -3 + 2x + -1x = 7 + 1x + -1x Combine like terms: 2x + -1x = 1x -3 + 1x = 7 + 1x + -1x Combine like terms: 1x + -1x = 0 -3 + 1x = 7 + 0 -3 + 1x = 7 Add '3' to each side of the equation. -3 + 3 + 1x = 7 + 3 Combine like terms: -3 + 3 = 0 0 + 1x = 7 + 3 1x = 7 + 3 Combine like terms: 7 + 3 = 10 1x = 10 Divide each side by '1'. x = 10 Simplifying x = 10
| 3(5x-12)=69 | | 2-2x=x-16 | | (-10x)(-3)= | | 8(-3b+7)=-136 | | 6+6+6+6+6+6= | | -9+y=-2 | | 5m-1=5+2m-8m+16 | | 2=3+u | | -9+z=37 | | 14+6x=7x+8 | | 3x+2x+30= | | 40-(2x+14)=2(x+8)+x | | -7(1+3n)=-112 | | 7x-2=110000000000 | | -2v+4v=12+5v | | 7x-2=11000000 | | 6n^2-7=0 | | 2n+3.4=5.8 | | 5x-8+3y=180 | | 25x-7-16x+4=22x-6-13x+11 | | 16-6=-n | | 3(5x-12)=6g | | 3(1x+4)+5x=-20 | | 4(1+6x)=-140 | | 5x-8+132=180 | | 3x^3+15x^2+9x-5=0 | | 19284734x-91203=92 | | y^2+y=8 | | Y=x^3-12x+17 | | -6-3n=-7n-6+4n | | -6(x-4)=-4(x-8) | | x+(x+1)+(x+2)=-75 |